Live-cell imaging reveals decreased cAMP in a PFE-associated c.1050-3C>G PTH1R cell model - K. Marnet; H. Subramanian; M. Wiesler; A. Borst; D. Liedtke; G. Pattappa; D. Docheva; V. O. Nikolaev; A. Stellzig-Eisenhauer; M. Eigenthaler; M. Herrmann (Journal of Molecular Medicine, 2026)
Primary failure of eruption (PFE) is a rare autosomal disorder provoked by heterozygous mutations in the parathyroid hormone receptor 1 ( PTH1R ) gene. PTH1R is a G protein-coupled receptor (GPCR) which regulates intracellular signaling molecules like cAMP. By using CRISPR/Cas9, the pathogenic PTH1R variant, c.1050-3C>G, was introduced into the periodontal ligament (PDL-hTERT) cell line to investigate molecular mechanisms in a PFE in vitro model. The PDL-hTERT immortal cell line, derived from human primary PDL cells, is a well-established model for dental diseases and expresses PTH1R . We performed different functional assays to compare the behavior of the PDL-hTERT WT versus PTH1R -mutated cells. cAMP synthesis and PKA activation were compared between different cell lines by live-cell imaging using Förster Resonance Energy Transfer (FRET)-based biosensors. Phosphorylation of VASP was measured to validate and compare the PKA activation between the cell lines. In summary, our experiments show that the mutated cell line has no major phenotypic changes, but the PTH1R downstream signaling cascade is impaired. Key messages A rare autosomal disorder linked to mutations in the PTH1R gene, which encodes a G protein-coupled receptor regulating intracellular signaling, including cAMP production. The pathogenic PTH1R mutation (c.1050-3C>G) was introduced into a periodontal ligament (PDL hTERT) cell line to model PFE and study molecular mechanisms in vitro. Functional assay revealed that while the mutated cell line displayed no major phenotypic changes, the PTH1R downstream signaling cascade, including cAMP synthesis and PKA activation, was disrupted. Techniques like FRET-based biosensors and VASP phosphorylation assays highlighted specific impairments in signaling pathways in cells with the PTH1R mutations

Present-Day Sea Level Variations in Coastal Areas from Daily to Multidecadal Time Scales: Observations and Causes - A. Cazenave; R. Almar; P. Almeida; N. K. Ayoub; J. H. Bettencourt; F. Birol; W. Han; M. Herrmann; S. Jevrejeva; L. Leclercq; F. Niño; J. Oelsmann; et al. (Surveys in Geophysics, 2026)

Quantifying microplastics and their retention in greywater treatment systems of different scales - M. Sami; A. Hedström; H. Österlund; E. Kvarnström; P.D. Jenssen; M. Hartl; I. Herrmann (Journal of Hazardous Materials, 2026)

A rapid and robust translational model for testicular aging research - N. Schmid; Y. Stepanov; M. Offner; L. Scholz; C. Herrmann; S. Petkov; R. Behr; J. B. Stöckl; T. Fröhlich; A. Mayerhofer (Histochemistry and Cell Biology, 2026)
In humans, testicular peritubular cells (TPCs) form a small compartment surrounding the seminiferous tubules and, as shown previously, undergo age-related changes. How they may contribute to the age-associated decline of testicular functions is not well known. Likewise, the mechanisms of testicular aging in humans are not well examined. This is in part due to the lack of appropriate cellular models. We aimed to establish an aging model of TPCs, which is based on immortalized nonhuman primate (NHP) peritubular cells (iMKTPCs) from Callithrix jacchus . As shown previously by a comprehensive proteomic approach, they strongly resemble human TPCs but lack the human cell-intrinsic heterogeneity. Cellular senescence was robustly induced within 10 days upon exposure to 25 µg/mL bleomycin for 24 h. This resulted in increased β-galactosidase activity, enlarged cells, and elevated transcript levels of senescence-associated secretory phenotype (SASP) molecules ( IL1b , TNFa , CCL2 ). The ability to contract upon a stimulus was reduced, as shown in live cell imaging studies. Reduced proliferation among others was indicated by a decreased abundance of proliferating cell nuclear antigen (PCNA), evident in a proteomic analysis, which also revealed massive changes (341 significantly increased and 372 decreased proteins). Bioinformatics analysis indicated a marked reduction in several cell-motility–associated proteins, whereas proteins linked to extracellular exosomes, the cytoskeleton, and lysosomal pathways were increased in abundance. To conclude, bleomycin treatment causes a rapid and robust induction of cellular senescence in a translational testicular cell model of peritubular cells. This model will enable future studies aiming to explore mechanisms and consequences of testicular aging.

Pre- and post-harvest spectral estimation of carnosic acid and rosmarinic acid in rosemary - A. Mishra; A. Krief; M.M. Sahoo; A. Schachter; I. Gonda; N. Dudai; T. Trigano; I. Herrmann (Computers and Electronics in Agriculture, 2026)

Factors affecting 87Sr/86Sr preservation in conodont apatite: An example from the Ordovician of Baltoscandia - Christopher T. Conwell; Matthew R. Saltzman; Anders Lindskog; Mats E. Eriksson; Elizabeth M. Griffith; Stephen A. Leslie; Cole T. Edwards; Olle Hints; Achim D. Herrmann (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Rebuttal to the response by Millar and Broadhurst - Bent Herrmann; Juan Santos; Manu Sistiaga; Jure Brčić; Junita D. Karlsen; Valentina Melli; Antonello Sala; Tiago Veiga-Malta; Jesse Brinkhof; Andrea Petetta; Mengjie Yu; Mark J.M. Lomeli; et al. (Fisheries Research, 2026)

A fundamental trade‐off among resilience, resistance, efficiency, and redundancy in tidal wetlands - Joshua E. Lerner; Rusty A. Feagin; Thomas P. Huff; Raymond G. Najjar; Astrid Layton; Maria Herrmann; Jose D. Fuentes (Ecology, 2026)
In an era of change, the survival and adaptability of ecosystems will be tested. An optimal ecosystem would be both resistant and resilient to negative disturbance but also efficient and redundant in its growth when given positive subsidies. However, initial evidence has suggested that these properties cannot all be maximized at the same time, and so we sought to quantitatively assess whether there are fundamental trade‐offs between them at the ecosystem level. To achieve this aim, we used a 250‐m resolution NASA MODIS dataset of gross primary productivity (GPP) to monitor 145,871 tidal wetland locations across the conterminous United States every 16 days from March 2000 to December 2020. We quantified the size and duration of the perturbation events in tidal wetland GPP ( n = 13,754,386) and modeled their frequency distributions. Event sizes and recurrence intervals were exponentially distributed and event durations were closely modeled by an inverse power law. This scale‐free manner through which tidal wetlands dissipated perturbations to their GPP flux provided them with long‐term stability across a wide range of geography. We also found that a tidal wetland's positive event responses traded off between properties of efficiency and redundancy, its negative events traded off between resistance and resilience, and that all four properties were orthogonally related to one another. We then constructed a conceptual model to help understand the potential mechanism behind this four‐quadrant trade‐off. The trade‐off appeared to be driven by a feedback between the waiting time and magnitude of positive and negative events, the duration of their effects, and the environmental and physical constraints limiting an ecosystem's growth and productivity. In summary, we detail an emergent pattern of trade‐offs and constraints associated with how tidal wetland ecosystems respond to both positive and negative perturbations in carbon flux.

Phenological Plasticity and Its Temperature‐Related Drivers in Common Songbirds Across Europe - Paul Cuchot; Timothée Bonnet; Robert A. Robinson; Juan Arizaga; Wolfgang Fiedler; Olaf Geiter; Ian Henshaw; Christof Herrmann; Henk van der Jeugd; Zsolt Karcza; Arantza Leal; Petteri Lehikoinen; et al. (Global Change Biology, 2025)
Phenological plasticity—the ability of organisms to adjust the timing of life‐history events in response to environmental variability—is the primary adaptive mechanism for many organisms to changing seasonality (e.g., earlier spring). By enabling alignment between life‐history events and resource availability, it helps to maintain fitness despite changing environmental conditions. Theory predicts that phenological plasticity should vary among populations because of heterogeneity in environmental variability, and among species because of differences in life‐history (e.g., migration distance) and phylogenetic constraints. However, comprehensive, multi‐species, and cross‐population analyses of phenological plasticity remain scarce. Here, we address this gap by using a unique, four‐decade dataset from Europe‐wide monitoring of common songbirds. Our approach reveals how variation in phenological plasticity is structured according to site temperature properties, both within and across species. We found that long‐distance migrants generally exhibit lower plasticity than residents or short‐distance migrants, highlighting a fundamental constraint tied to migration strategy. Within species, populations inhabiting sites with predictable temperature profiles showed slightly stronger plastic responses, particularly among single‐brooded species and those adapted to warmer breeding conditions. Notably, populations from the fastest‐warming regions demonstrated marginally greater plasticity, regardless of other ecological traits, suggesting a global tendency for increased responsiveness in rapidly changing climates. These findings confirm and extend patterns previously observed at smaller scales, offering a more nuanced understanding of how local temperature conditions drive phenological plasticity. By demonstrating that the interplay between local environmental conditions and life‐history traits underpins variation in breeding phenological responses, our study refines the current framework for predicting adaptive potential across populations and species under climate change.

Temporal Changes to Migratory Fuel Load in Migratory Birds Across Europe - Jennifer Anne Border; Robert A. Robinson; James W. Pearce‐Higgins; Chris M. Hewson; Christine Howard; Philip A. Stephens; Stephen G. Willis; Jan A. C. von Rönn; Pierre‐Yves Henry; Romain Lorrilliere; Lorenzo Serra; Simona Imperio; et al. (Global Change Biology, 2025)
Climate change is a major threat to biodiversity, and migratory animals are particularly vulnerable, due partly to their reliance upon good resource availability across a network of sites at specific times. Migrants perform vital ecosystem functions, transferring significant resources across large spatial scales, but the impacts of climate change on the ability of individuals to complete these journeys are poorly studied. Collecting the large‐scale and long‐term data on the condition of individuals during migration to address this is challenging, but in migratory birds, we have a model system for which a large network of ringers (banders) collect individual data on body size and mass, enabling variation in body condition to be tracked. We used long‐term ringing data on 33 Afro–Palearctic migratory bird species at 286 sites across Europe to demonstrate a large‐scale decrease in migratory fuel loads during autumn over the last 40 years, but not in spring. Declines were strongest across southern Europe and linked to rising temperatures. The timing of autumn fuelling has also shifted, occurring earlier at northern sites and later at southern sites. These relationships varied depending on diet and breeding cycle length. Obligate insectivores were more constrained by temperature in the timing and magnitude of fuelling than frugivores. Species with short breeding cycles departed later at southern sites in warmer years, likely reflecting an extended breeding season. Altogether, these latitudinally varying findings suggest a trade‐off between maximising productivity or maximising adult survival as climate drives changing constraints on breeding season length and resource availability. Similar climate‐induced trade‐offs may be happening in other migratory taxa with the potential to influence population trends.

Letter to the Editor re: Millar and Broadhurst (2025): “Incorrect inference from size-selectivity studies due to widespread misuse of bootstrap confidence bands” [Fisheries Research 281, 107225] - Bent Herrmann; Juan Santos; Manu Sistiaga; Jure Brčić; Junita D. Karlsen; Valentina Melli; Antonello Sala; Tiago Veiga-Malta; Jesse Brinkhof; Andrea Petetta; Mengjie Yu; Mark J.M. Lomeli; et al. (Fisheries Research, 2025)

Artificial intelligence-assisted Ki67 cell counting to aid canine cutaneous mast cell tumour prognostication - D. Walker; A. Herrmann; K. Erles; S. Haugland (Journal of Comparative Pathology, 2025)

Contrasting trends in wheat production exist across Australia in response to climate - Roger A. Lawes; Rose Roche; Rebecca O. Darbyshire; Aswin Singaram Natarajan; Chris M. Herrmann (European Journal of Agronomy, 2025)

P29-02 Comparative assessment of 24 poorly soluble, low toxicity dusts after short-term exposure - A. Herrmann; L. Puente; M. Dammann; L. Ma-Hock; H. Stratmann (Toxicology Letters, 2025)

ICESat-2 bathymetry algorithms: A review of the current state-of-the-art and future outlook - Jaehoon Jung; Christopher E. Parrish; Lori A. Magruder; Joan Herrmann; Suhong Yoo; Jeffrey S. Perry (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Hard-seeded annual pasture legume phases are a profitable and low risk option in mixed farming regions with low to medium rainfall - Dean T. Thomas; Sadeeka L. Jayasinghe; Chris Herrmann; Robert J. Harrison; Bonnie M. Flohr; Roger A. Lawes (Agricultural Systems, 2025)

Rapid subsidence as a driver of phosphate deposition in the later Ordovician: Case study from the Alabama Appalachians - John T. Haynes; Rafael A. Villanueva; Richard M. Robinet; Stephen A. Leslie; Achim D. Herrmann (Sedimentary Geology, 2025)

Glyphosate losses through various stages of coffee production and consequences for human exposure - Gerhard Bytof; Oliver Suesse-Herrmann; Meike Holtmann; Jessica A. Falenski; Viviane Theurillat; Gerhard Eisenbrand (Food Additives & Contaminants: Part A, 2025)

Using species-specific behavior to improve catch efficiency of target species in mixed trawl fisheries - Ludvig A. Krag; Rikke P. Frandsen; Bent Herrmann; Grete E. Dinesen; Junita D. Karlsen (Fisheries Research, 2025)

Can pots be an alternative fishing gear to gillnets? A Mediterranean case study - M. Virgili; A. Petetta; B. Herrmann; K. Cerbule; S. Guicciardi; G. La Manna; L. Malvarosa; D. Li Veli; G. Barone; A. Lucchetti (Reviews in Fish Biology and Fisheries, 2024)
Small-scale coastal fisheries in the Mediterranean often employ gillnets, a widely used gear worldwide. The disadvantages of gillnets in this fishery include high bycatch levels of unwanted species and consequent discards. Moreover, spatial conflict with other gears and dolphin depredation often results in considerable economic loss. Alternative fishing methods are being tested. This study investigated whether, in small-scale fisheries in the Adriatic Sea, pots can ensure sustainable harvest of mantis shrimp ( Squilla mantis ), a major target demersal species in terms of landings, and possibly replace traditional gillnets. We adopted a multidisciplinary approach to investigate the catch efficiency, biological impact, and socio-economic effects of the two fishing methods. We found different species compositions in gillnet and pot catches. Gillnets yielded a greater number of discarded species of no commercial value, whereas pots caught a greater amount of mantis shrimp. Finally, a profit analysis indicated that pot fishery has the potential to increase profits for the commercial fishing industry. This study suggests that pots provide a more sustainable fishing method, both in terms of revenue and environmental impact.

A structured approach for the compliance analysis of battery systems with regard to the new EU Battery Regulation - Sönke Hansen; Tom Rüther; Mark Mennenga; Christoph Helbig; Gregor Ohnemüller; Filip Vysoudil; Constantin Wolf; Bernd Rosemann; Sandra Pavón; Alexander Michaelis; Thomas Vietor; Frank Döpper; et al. (Resources, Conservation and Recycling, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Longitudinal relationships between depressive symptoms, functional impairment, and physical activity in later late life - Lisa Y. Xiong; Madeline Wood Alexander; Hugo Cogo-Moreira; Che-Yuan Wu; Michael Eid; Nathan Herrmann; Damien Gallagher; Jodi D. Edwards; Krista L. Lanctôt; Susan Marzolini; David A. Bennett; Jennifer S. Rabin; et al. (GeroScience, 2024)

Population balance modeling-assisted prediction of oxygen mass transfer coefficients with optical measurements - R. Herrmann-Heber; M. Oleshova; S.F. Reinecke; M. Meier; S. Taş; U. Hampel; A. Lerch (Journal of Water Process Engineering, 2024)

Study of thermal and photochemical aging of saturates, naphtenic-aromatics, resins, and asphaltene fractions of asphalt cement by FTIR and FT-ICR MS - Natã C.L. Madeira; Lindamara M. de Souza; Alan Reinke Pereira; Luiz S. Chinelatto; Margareth C.C. Cravo; Luis A. Herrmann do Nascimento; Valdemar Lacerda; Wanderson Romão (Fuel, 2024)

Beyond growth: The significance of non-growth anabolism for microbial carbon-use efficiency in the light of soil carbon stabilisation - Tobias Bölscher; Cordula Vogel; Folasade K. Olagoke; Katharina H.E. Meurer; Anke M. Herrmann; Tino Colombi; Melanie Brunn; Luiz A. Domeignoz-Horta (Soil Biology and Biochemistry, 2024)

Neurophysiological and other features of working memory in older adults at risk for dementia - Rachel A. Patterson; Heather Brooks; Mina Mirjalili; Neda Rashidi-Ranjbar; Reza Zomorrodi; Daniel M. Blumberger; Corinne E. Fischer; Alastair J. Flint; Ariel Graff-Guerrero; Nathan Herrmann; James L. Kennedy; Sanjeev Kumar; et al. (Cognitive Neurodynamics, 2024)

Lithospheric- and crustal-scale controls on variations in foreland basin development in the Northern Alpine Foreland Basin - Lucas H.J. Eskens; Nevena Andrić-Tomašević; Peter M. Süss; Matthias Müller; Rolf Herrmann; Todd A. Ehlers (Tectonophysics, 2024)

No effect on biological or chemical soil properties when amended with effective microorganisms for improved cover crop decomposition - Simon Oberholzer; Christa Herrmann; Natacha Bodenhausen; Hans-Martin Krause; Adrien Mestrot; Chinwe Ifejika Speranza; Klaus A. Jarosch (Applied Soil Ecology, 2024)

Adapting E-cigarette prevention programming to reach the latinx community - Alison K. Herrmann; Sylvia Lopez Ferullo; Miriam Hernandez; Verónica Arciga Barriga; Bernadett Leggis; Julissa Ruiz; Beth A. Glenn; Roshan Bastani (Cancer Causes & Control, 2024)
Purpose E-cigarettes are the most commonly used tobacco product among youth in the United States. Yet evidence-based prevention programming is limited due to the rapid onset of this threat. Community-based efforts to address vaping largely target youth in school settings. Although parents can play an important role in youth tobacco control efforts, messages about the dangers of vaping, use among adolescents, and strategies for intervening have not reached many Spanish-speaking parents in low-income Latinx communities. Our community-academic team developed e-cigarette prevention programming for use by promotor/as de salud to address this unmet need. Methods During the 1-year project, the team worked closely with a Project Advisory Committee to: review existing evidence-informed materials; conduct focus groups with parents, youth and promotor/as to guide program development; develop a curriculum to prepare promotor/as to educate low-literacy, Spanish-speaking parents about vaping; craft Spanish language resources for promotor/as to use in community education sessions; train 61 promotor/as to deliver the program; and support program delivery to 657 community members. Results Focus groups with promotor/as and community members, key-informant interviews, and brief surveys informed program development and assessment. Community member feedback was essential to development of appropriate materials. Promotor/as demonstrated significant pre- to post- training increases in e-cigarette knowledge and confidence in delivering vaping prevention education. Community members demonstrated a mastery of basic e-cigarette concepts and expressed intention to discuss vaping with their children. Conclusions Promotor/a-led programming for parents represents a promising approach to vaping prevention and control in the Latinx community.

Isolating the drivers of the species‐area relationship in experimental habitat islands - Granger W. Hanks; Natalie A. Clay; Maggie Herrmann; Clifton Nunnally; S. River D. Bryant; Craig R. McClain (Journal of Biogeography, 2024)
Aim Considered one of ecology's laws, the species‐area relationship (SAR) is among the most intensively studied ecological phenomena, yet the mechanisms through which the SAR arises and under what circumstances remain poorly understood. Here, we experimentally test the effects of area alone in the absence of commonly invoked mechanistic drivers of the SAR in both sub‐tidal bay and inter‐tidal marsh habitats. Location Louisiana, U.S.A. Taxon Invertebrate macrofauna. Methods To determine if surface area alone may generate the SAR, we conducted a small‐scale, ephemeral habitat island experiment in a subtidal soft‐bottom bay and in an intertidal soft‐bottom coastal salt marsh. Cellulose sponge habitat islands of varying surface areas, but with constant energy content and habitat diversity, were deployed in each location to isolate the effects of surface area on the SAR in the absence of species‐energy relationships and habitat diversity. Results Area alone, likely through passive sampling, generated significant SARs in both habitats, with the salt marsh producing the strongest relationship, likely due to differential physical structuring between habitats. Communities of low surface area sponges were generally nested within those of high surface area sponges, and dispersal limitation may have increased the importance of nestedness relative to species replacements in structuring communities between habitats. Main Conclusions That area alone, in the absence of covariates such as energy availability and habitat diversity may, significantly impact the species richness of experimental and ephemeral marine benthic habitat island communities. Our methodology may provide a new avenue for SAR research, allowing for the isolation and simultaneous testing of potential drivers through the physical manipulation of ephemeral habitats.

A genomic test of subspecies in the Eunota togata species group (Coleoptera: Cicindelidae): Morphology masks evolutionary relationships and taxonomy - Robert A. Laroche; Daniel P. Duran; Cin-Ty A. Lee; William Godwin; Stephen J. Roman; David P. Herrmann; Scott P. Egan (Molecular Phylogenetics and Evolution, 2023)

Do ticks exhibit repeatable individual behaviors? - Hugh Lefcort; Matthew L. Hovancsek; Lindsey A. Bell; Erin K. Ellinwood; Elizabeth M. Freisinger; Katelin G. Herrmann; Jalisa R. Lau (Experimental and Applied Acarology, 2023)

Model-parallel Fourier neural operators as learned surrogates for large-scale parametric PDEs - Thomas J. Grady; Rishi Khan; Mathias Louboutin; Ziyi Yin; Philipp A. Witte; Ranveer Chandra; Russell J. Hewett; Felix J. Herrmann (Computers & Geosciences, 2023)

Cadmium Reduction in Spring Wheat: Root Exudate Composition Affects Cd Partitioning Between Roots and Shoots - M. C. Affholder; A. A. Moazzami; M. Weih; H. Kirchmann; A. M. Herrmann (Journal of Soil Science and Plant Nutrition, 2023)
Cadmium (Cd) in cereals is one of the major sources of Cd intake by human diets, and solutions to reduce Cd concentrations in wheat still need to be developed. Plant breeding, by selecting low-Cd varieties, can be an important tool to reduce Cd in crops. Knowing the genotypic variation in Cd accumulation and furthering our understanding of the impact of root exudates composition on Cd accumulation in crops may provide valuable information for plant breeding. In this study, we selected nine spring wheat varieties and analysed the accumulation and distribution of Cd in shoots, roots, root surfaces and kernels in relation to their qualitative and quantitative composition of root exudates, determined by 1 H-NMR (Proton Nuclear Magnetic Resonance). Results showed that the Cd concentration in shoots at an early stage could be used as a predictor for Cd concentration in kernels. Total Cd uptake was not correlated to the mobility of Cd in the rhizosphere, but total Cd was negatively correlated to Cd adsorbed at the root surface. Furthermore, (i) exudation of organic acids (primarily succinate and acetate) increased Cd concentration in shoots, and (ii) exudation of nucleosides, DNA (deoxyribonucleic acid) degradation products, increased Cd adsorption at the root surface. Therefore, root exudates composition should be taken into account when selecting for low-Cd wheat traits.

Greywater treatment in a green wall using different filter materials and hydraulic loading rates - M. Sami; A. Hedström; E. Kvarnström; D.T. McCarthy; I. Herrmann (Journal of Environmental Management, 2023)

Influence of soil geomorphic factors on vegetation patterns in a model white sands ecosystem complex - Melissa A. Atwell; Mark N. Wuddivira; Sabine Fiedler; Mike Oatham; Ludger Herrmann; Bjoern Glasner; Vanessa Vetter; Hermann F. Jungkunst (CATENA, 2023)

Levels of nitrate, nitrite and nitrosamines in model sausages during heat treatment and in vitro digestion – The impact of adding nitrite and spinach (Spinacia oleracea L.) - Agnieszka A. Niklas; Grethe Iren A. Borge; Rune Rødbotten; Ingunn Berget; Mette H.B. Müller; Susan S. Herrmann; Kit Granby; Bente Kirkhus (Food Research International, 2023)

Genetic mapping of the powdery mildew resistance gene Pm7 on oat chromosome 5D - Sophie Brodführer; Volker Mohler; Melanie Stadlmeier; Sylwia Okoń; Steffen Beuch; Martin Mascher; Nicholas A. Tinker; Wubishet A. Bekele; Bernd Hackauf; Matthias Heinrich Herrmann (Theoretical and Applied Genetics, 2023)
Key message Three independent experiments with different genetic backgrounds mapped the resistance gene Pm7 in the oat genome to the distal part of the long arm of chromosome 5D. Abstract Resistance of oat to Blumeria graminis DC. f. sp. avenae is an important breeding goal in Central and Western Europe. In this study, the position of the effective and widely used resistance gene Pm7 in the oat genome was determined based on three independent experiments with different genetic backgrounds: genome-wide association mapping in a diverse set of inbred oat lines and binary phenotype mapping in two bi-parental populations. Powdery mildew resistance was assessed in the field as well as by detached leaf tests in the laboratory. Genotyping-by-sequencing was conducted to establish comprehensive genetic fingerprints for subsequent genetic mapping experiments. All three mapping approaches located the gene to the distal part of the long arm of chromosome 5D in the hexaploid oat genome sequences of OT3098 and ‘Sang.’ Markers from this region were homologous to a region of chromosome 2Ce of the C-genome species, Avena eriantha , the donor of Pm7 , which appears to be the ancestral source of a translocated region on the hexaploid chromosome 5D.

Sodium as a subsidy in the spring: evidence for a phenology of sodium limitation - Natalie A. Clay; Maggie C. Herrmann; Michelle A. Evans-White; Sally A. Entrekin; Colton West (Oecologia, 2023)
Understanding the factors that mediate carbon (C) cycling is increasingly important as anthropogenic activities and climate change alter ecosystems. Decomposition rates mediate C cycling and are in part regulated by sodium (Na) where Na is limiting up to some threshold after which Na becomes stressful and reduces decomposition rates (i.e., the Sodium Subsidy-Stress hypothesis). An overlooked pathway by which decomposers encounter increased salts like NaCl is through plants, which often take up Na in proportion to soil concentrations. Here we tested the hypothesis that Na addition through litter (detritus) and water and their interaction would impact detrital processing and leachate chemistry. Laboratory riparian soil mesocosms received either artificial litter (100% cellulose sponges) soaked in 0.05% NaCl (NaCl L ) or just H 2 O (H 2 O L : control) and half of each litter treatment received weekly additions of 150 ml of either 0.05% NaCl water (NaCl W ) or just H 2 O (H 2 O W : control). After 8 weeks decomposition was higher in NaCl addition treatments (both NaCl L and NaCl W and their combo) than controls (H 2 O L + H 2 O W ) but reflected a unimodal relationship where the saltiest treatment (NaCl L + NaCl W ) was only marginally higher than controls indicating a subsidy-stress response. Previous studies in this system found that Na addition in either water or litter decreased decomposition. However, differences may reflect a phenology of Na demand where Na-limitation increases in the spring (this study). These results indicate that our understanding of how Na impacts detrital processes, C cycling, and aquatic-terrestrial linkages necessitates incorporation of temporal dynamics.

Joint effects of climate, tree size, and year on annual tree growth derived from tree‐ring records of ten globally distributed forests - Kristina J. Anderson‐Teixeira; Valentine Herrmann; Christine R. Rollinson; Bianca Gonzalez; Erika B. Gonzalez‐Akre; Neil Pederson; M. Ross Alexander; Craig D. Allen; Raquel Alfaro‐Sánchez; Tala Awada; Jennifer L. Baltzer; Patrick J. Baker; et al. (Global Change Biology, 2022)
Tree rings provide an invaluable long‐term record for understanding how climate and other drivers shape tree growth and forest productivity. However, conventional tree‐ring analysis methods were not designed to simultaneously test effects of climate, tree size, and other drivers on individual growth. This has limited the potential to test ecologically relevant hypotheses on tree growth sensitivity to environmental drivers and their interactions with tree size. Here, we develop and apply a new method to simultaneously model nonlinear effects of primary climate drivers, reconstructed tree diameter at breast height (DBH), and calendar year in generalized least squares models that account for the temporal autocorrelation inherent to each individual tree's growth. We analyze data from 3811 trees representing 40 species at 10 globally distributed sites, showing that precipitation, temperature, DBH, and calendar year have additively, and often interactively, influenced annual growth over the past 120 years. Growth responses were predominantly positive to precipitation (usually over ≥3‐month seasonal windows) and negative to temperature (usually maximum temperature, over ≤3‐month seasonal windows), with concave‐down responses in 63% of relationships. Climate sensitivity commonly varied with DBH (45% of cases tested), with larger trees usually more sensitive. Trends in ring width at small DBH were linked to the light environment under which trees established, but basal area or biomass increments consistently reached maxima at intermediate DBH. Accounting for climate and DBH, growth rate declined over time for 92% of species in secondary or disturbed stands, whereas growth trends were mixed in older forests. These trends were largely attributable to stand dynamics as cohorts and stands age, which remain challenging to disentangle from global change drivers. By providing a parsimonious approach for characterizing multiple interacting drivers of tree growth, our method reveals a more complete picture of the factors influencing growth than has previously been possible.

Parasites of chinstrap penguins (Pygoscelis antarctica) from three localities in the Antarctic Peninsula and a review of their parasitic fauna - Daniel A. González-Acuña; Lucila Moreno; Michelle Wille; Bjorn Herrmann; Mike J. Kinsella; Ricardo L. Palma (Polar Biology, 2021)

The EU chemicals strategy for sustainability: in support of the BfR position - Frank A. Barile; Sir Colin Berry; Bas Blaauboer; Alan Boobis; Herrmann M. Bolt; Christopher Borgert; Wolfgang Dekant; Daniel Dietrich; Jose L. Domingo; Corrado L. Galli; Gio Batta Gori; Helmut Greim; et al. (Archives of Toxicology, 2021)
The EU chemicals strategy for sustainability (CSS) asserts that both human health and the environment are presently threatened and that further regulation is necessary. In a recent Guest Editorial, members of the German competent authority for risk assessment, the BfR, raised concerns about the scientific justification for this strategy. The complexity and interdependence of the networks of regulation of chemical substances have ensured that public health and wellbeing in the EU have continuously improved. A continuous process of improvement in consumer protection is clearly desirable but any initiative directed towards this objective must be based on scientific knowledge. It must not confound risk with other factors in determining policy. This conclusion is fully supported in the present Commentary including the request to improve both, data collection and the time-consuming and bureaucratic procedures that delay the publication of regulations.

Regional Gas Transport During Conventional and Oscillatory Ventilation Assessed by Xenon-Enhanced Computed Tomography - Jacob Herrmann; Sarah E. Gerard; Joseph M. Reinhardt; Eric A. Hoffman; David W. Kaczka (Annals of Biomedical Engineering, 2021)

Composition and compound proportions affect the response to complex chemical signals in a spiny lizard - Cristina Romero-Diaz; Stephanie M. Campos; Morgan A. Herrmann; Helena A. Soini; Milos V. Novotny; Diana K. Hews; Emília P. Martins (Behavioral Ecology and Sociobiology, 2021)

Long-Term Impacts of Invasive Insects and Pathogens on Composition, Biomass, and Diversity of Forests in Virginia’s Blue Ridge Mountains - Kristina J. Anderson-Teixeira; Valentine Herrmann; Wendy B. Cass; Alan B. Williams; Stephen J. Paull; Erika B. Gonzalez-Akre; Ryan Helcoski; Alan J. Tepley; Norman A. Bourg; Christopher T. Cosma; Abigail E. Ferson; Caroline Kittle; et al. (Ecosystems, 2021)

From empirical to theoretical models of light response curves - linking photosynthetic and metabolic acclimation - Helena A. Herrmann; Jean-Marc Schwartz; Giles N. Johnson (Photosynthesis Research, 2020)
Light response curves (LRCs) describe how the rate of photosynthesis varies as a function of light. They provide information on the maximum photosynthetic capacity, quantum yield, light compensation point and leaf radiation use efficiency of leaves. Light response curves are widely used to capture photosynthetic phenotypes in response to changing environmental conditions. However, models describing these are predominantly empirical and do not attempt to explain behaviour at a mechanistic level. Here, we use modelling to understand the metabolic changes required for photosynthetic acclimation to changing environmental conditions. Using a simple kinetic model, we predicted LRCs across the physiological temperature range of Arabidopsis thaliana and confirm these using experimental data. We use our validated metabolic model to make novel predictions about the metabolic changes of temperature acclimation. We demonstrate that NADPH utilization are enhanced in warm-acclimated plants, whereas both NADPH and CO 2 utilization is enhanced in cold-acclimated plants. We demonstrate how different metabolic acclimation strategies may lead to the same photosynthetic response across environmental change. We further identify that certain metabolic acclimation strategies, such as NADPH utilization, are only triggered when plants are moved beyond a threshold high or low temperature.

Human exposure to synthetic endocrine disrupting chemicals (S-EDCs) is generally negligible as compared to natural compounds with higher or comparable endocrine activity: how to evaluate the risk of the S-EDCs? - Herman Autrup; Frank A. Barile; Sir Colin Berry; Bas J. Blaauboer; Alan Boobis; Herrmann Bolt; Christopher J. Borgert; Wolfgang Dekant; Daniel Dietrich; Jose L. Domingo; Gio Batta Gori; Helmut Greim; et al. (Archives of Toxicology, 2020)
Theoretically, both synthetic endocrine disrupting chemicals (S-EDCs) and natural (exogenous and endogenous) endocrine disrupting chemicals (N-EDCs) can interact with endocrine receptors and disturb hormonal balance. However, compared to endogenous hormones, S-EDCs are only weak partial agonists with receptor affinities several orders of magnitude lower. Thus, to elicit observable effects, S-EDCs require considerably higher concentrations to attain sufficient receptor occupancy or to displace natural hormones and other endogenous ligands. Significant exposures to exogenous N-EDCs may result from ingestion of foods such as soy-based diets, green tea and sweet mustard. While their potencies are lower as compared to natural endogenous hormones, they usually are considerably more potent than S-EDCs. Effects of exogenous N-EDCs on the endocrine system were observed at high dietary intakes. A causal relation between their mechanism of action and these effects is established and biologically plausible. In contrast, the assumption that the much lower human exposures to S-EDCs may induce observable endocrine effects is not plausible. Hence, it is not surprising that epidemiological studies searching for an association between S-EDC exposure and health effects have failed. Regarding testing for potential endocrine effects, a scientifically justified screen should use in vitro tests to compare potencies of S-EDCs with those of reference N-EDCs. When the potency of the S-EDC is similar or smaller than that of the N-EDC, further testing in laboratory animals and regulatory consequences are not warranted.

Assessment of maize yield and phenology by drone-mounted superspectral camera - Ittai Herrmann; Eyal Bdolach; Yogev Montekyo; Shimon Rachmilevitch; Philip A. Townsend; Arnon Karnieli (Precision Agriculture, 2020)

Soluble Epoxide Hydrolase-Derived Linoleic Acid Oxylipins in Serum Are Associated with Periventricular White Matter Hyperintensities and Vascular Cognitive Impairment - Di Yu; Marie Hennebelle; Demetrios J. Sahlas; Joel Ramirez; Fuqiang Gao; Mario Masellis; Hugo Cogo-Moreira; Richard H. Swartz; Nathan Herrmann; Pak Cheung Chan; Jacqueline A. Pettersen; Donald T. Stuss; et al. (Translational Stroke Research, 2019)

Propiconazole induces abnormal behavior and oxidative stress in zebrafish - Jéssica Valadas; Ricieri Mocelin; Adrieli Sachett; Matheus Marcon; Régis A Zanette; Eliane Dallegrave; Ana P Herrmann; Angelo Piato (Environmental Science and Pollution Research, 2019)

Asymmetric interference competition and niche partitioning between native and invasive Anolis lizards - Katherine A. Culbertson; Nicholas C. Herrmann (Oecologia, 2019)

The efficiency of sieve‐panels for bycatch separation in Nephrops trawls - Juan Santos; Bent Herrmann; Bernd Mieske; Ludvig A. Krag; Stefanie Haase; Daniel Stepputtis (Fisheries Management and Ecology, 2018)
This study investigated the efficiency of a sieve‐panel concept, intended to separate bycatch species from Nephrops (Norway lobster) in a trawl gear via mechanical and behavioural means. Four different designs of varying panel mesh size or inclination were tested in experimental fishing. For each design, the length‐dependent sieving efficiency, defined as the fraction of Nephrops or fish passing through the panel to the lower codend, was estimated. The sieving efficiency for Nephrops increased from ~17% to ~71% as mesh size increased, and decreased with increasing carapace length, but did so less as panel inclination and mesh size increased. The sieving efficiency for roundfish was low, as intended, while the efficiency for flatfish decreased with fish size. Although results are promising, the sieving efficiency for the largest, most valuable Nephrops remained too low. Therefore, further improvements are necessary before the concept is acceptable to the commercial fishing fleet.

Effect of fish length and nutritional condition on the fecundity of distressed Atlantic cod Gadus morhua from the Baltic Sea - M. Mion; A. Thorsen; F. Vitale; J. Dierking; J. P. Herrmann; B. Huwer; B. von Dewitz; M. Casini (Journal of Fish Biology, 2018)
The disappearance of larger individuals and the decrease in individual body condition suffered by Atlantic cod Gadus morhua in the eastern Baltic during the past two decades can be expected to affect the stock reproductive output. To investigate this, female G. morhua were collected during the spawning and pre‐spawning period in 2015−2016. The current individual potential fecundity ( F P ) of eastern Baltic G. morhua was estimated and analysed in relation to total length ( L T ) and indices of nutritional status such as body condition ( K ) and hepato‐somatic index ( I H ) using generalized linear models. In addition, the current prevalence of atresia and its potential relation to K were investigated. Moreover, a calibration curve to estimate F P from oocyte diameter, based on the autodiametric oocyte counting method, was established for the first time for eastern Baltic G. morhua and can be used for future fecundity studies on this stock. The results showed that F P was mainly positively related to fish length, but K and I H also contributed significantly to the variation in F P . The model predicted that fish with K = 1·2 have a F P 51% higher than fish of the same L T with K = 0·8. The prevalence of fecundity regulation by atresia was 5·8%, but it was found only in fish in the pre‐spawning maturity stage and with low K . Temporal changes in biological features such as the length composition and individual body condition of eastern Baltic G. morhua , should be accounted for when estimating stock reproductive potential.

Measurements of PM10 ions and trace gases with the online system MARGA at the research station Melpitz in Germany – A five-year study - B. Stieger; G. Spindler; B. Fahlbusch; K. Müller; A. Grüner; L. Poulain; L. Thöni; E. Seitler; M. Wallasch; H. Herrmann (Journal of Atmospheric Chemistry, 2018)

Changes in motor performance and mental workload during practice of reaching movements: a team dynamics perspective - Isabelle M. Shuggi; Patricia A. Shewokis; Jeffrey W. Herrmann; Rodolphe J. Gentili (Experimental Brain Research, 2018)

The spatial distribution of soil organic carbon in tidal wetland soils of the continental United States - Audra L. Hinson; Rusty A. Feagin; Marian Eriksson; Raymond G. Najjar; Maria Herrmann; Thomas S. Bianchi; Michael Kemp; Jack A. Hutchings; Steve Crooks; Thomas Boutton (Global Change Biology, 2017)
Tidal wetlands contain large reservoirs of carbon in their soils and can sequester carbon dioxide ( CO 2 ) at a greater rate per unit area than nearly any other ecosystem. The spatial distribution of this carbon influences climate and wetland policy. To assist with international accords such as the Paris Climate Agreement, national‐level assessments such as the United States (U.S.) National Greenhouse Gas Inventory, and regional, state, local, and project‐level evaluation of CO 2 sequestration credits, we developed a geodatabase (CoBluCarb) and high‐resolution maps of soil organic carbon ( SOC ) distribution by linking National Wetlands Inventory data with the U.S. Soil Survey Geographic Database. For over 600,000 wetlands, the total carbon stock and organic carbon density was calculated at 5‐cm vertical resolution from 0 to 300 cm of depth. Across the continental United States, there are 1,153–1,359 Tg of SOC in the upper 0–100 cm of soils across a total of 24 945.9 km 2 of tidal wetland area, twice as much carbon as the most recent national estimate. Approximately 75% of this carbon was found in estuarine emergent wetlands with freshwater tidal wetlands holding about 19%. The greatest pool of SOC was found within the Atchafalaya/Vermilion Bay complex in Louisiana, containing about 10% of the U.S. total. The average density across all tidal wetlands was 0.071 g cm −3 across 0–15 cm, 0.055 g cm −3 across 0–100 cm, and 0.040 g cm −3 at the 100 cm depth. There is inherent variability between and within individual wetlands; however, we conclude that it is possible to use standardized values at a range of 0–100 cm of the soil profile, to provide first‐order quantification and to evaluate future changes in carbon stocks in response to environmental perturbations. This Tier 2‐oriented carbon stock assessment provides a scientific method that can be copied by other nations in support of international requirements.

Prolonged suppressive antibiotic therapy for prosthetic joint infection in the elderly: a national multicentre cohort study - V. Prendki; T. Ferry; P. Sergent; E. Oziol; E. Forestier; T. Fraisse; S. Tounes; S. Ansart; J. Gaillat; S. Bayle; O. Ruyer; F. Borlot; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Peripheral Alterations in Cytokine and Chemokine Levels After Antidepressant Drug Treatment for Major Depressive Disorder: Systematic Review and Meta-Analysis - Cristiano A. Köhler; Thiago H. Freitas; Brendon Stubbs; Michael Maes; Marco Solmi; Nicola Veronese; Nayanna Q. de Andrade; Gerwyn Morris; Brisa S. Fernandes; André R. Brunoni; Nathan Herrmann; Charles L. Raison; et al. (Molecular Neurobiology, 2017)

Evaluation of nutria (Myocastor coypus) detection methods in Maryland, USA - Margaret A. Pepper; Valentine Herrmann; James E. Hines; James D. Nichols; Stephen R. Kendrot (Biological Invasions, 2017)

Efficacy of cold fogging and oral herbal extracts on air quality and immune response of broilers - Awad A. Shehata; Klaus Herrmann; Thomas Pfalz; Hafez M. Hafez; Wieland Schrödl; Monika Krüger (Aerobiologia, 2017)

The role of digital data entry in participatory environmental monitoring - Jeremy R. Brammer; Nicolas D. Brunet; A. Cole Burton; Alain Cuerrier; Finn Danielsen; Kanwaljeet Dewan; Thora Martina Herrmann; Micha V. Jackson; Rod Kennett; Guillaume Larocque; Monica Mulrennan; Arun Kumar Pratihast; et al. (Conservation Biology, 2016)
Many argue that monitoring conducted exclusively by scientists is insufficient to address ongoing environmental challenges. One solution entails the use of mobile digital devices in participatory monitoring (PM) programs. But how digital data entry affects programs with varying levels of stakeholder participation, from nonscientists collecting field data to nonscientists administering every step of a monitoring program, remains unclear. We reviewed the successes, in terms of management interventions and sustainability, of 107 monitoring programs described in the literature (hereafter programs) and compared these with case studies from our PM experiences in Australia, Canada, Ethiopia, Ghana, Greenland, and Vietnam (hereafter cases). Our literature review showed that participatory programs were less likely to use digital devices, and 2 of our 3 more participatory cases were also slow to adopt digital data entry. Programs that were participatory and used digital devices were more likely to report management actions, which was consistent with cases in Ethiopia, Greenland, and Australia. Programs engaging volunteers were more frequently reported as ongoing, but those involving digital data entry were less often sustained when data collectors were volunteers. For the Vietnamese and Canadian cases, sustainability was undermined by a mismatch in stakeholder objectives. In the Ghanaian case, complex field protocols diminished monitoring sustainability. Innovative technologies attract interest, but the foundation of effective participatory adaptive monitoring depends more on collaboratively defined questions, objectives, conceptual models, and monitoring approaches. When this foundation is built through effective partnerships, digital data entry can enable the collection of more data of higher quality. Without this foundation, or when implemented ineffectively or unnecessarily, digital data entry can be an additional expense that distracts from core monitoring objectives and undermines project sustainability. The appropriate role of digital data entry in PM likely depends more on the context in which it is used and less on the technology itself.

HC-Induced Deactivation in CO Conversion at Diesel Oxidation Catalysts - M. Herrmann; S. Malmberg; A. Drochner; H. Vogel; R. Hayes; M. Votsmeier (Emission Control Science and Technology, 2016)

EPMA-World Congress 2015 - Jella-Andrea Abraham; Olga Golubnitschaja; Ildar Akhmetov; Russell J. Andrews; Leonidas Quintana; Russell J. Andrews; Babak Baban; Jun Yao Liu; Xu Qin; Tailing Wang; Mahmood S. Mozaffari; Viktoriia V. Bati; et al. (EPMA Journal, 2016)

Connectivity from a different perspective: comparing seed dispersal kernels in connected vs. unfragmented landscapes - John D. Herrmann; Tomás A. Carlo; Lars A. Brudvig; Ellen I. Damschen; Nick M. Haddad; Douglas J. Levey; John L. Orrock; Joshua J. Tewksbury (Ecology, 2016)
Habitat fragmentation can create significant impediments to dispersal. A technique to increase dispersal between otherwise isolated fragments is the use of corridors. Although previous studies have compared dispersal between connected fragments to dispersal between unconnected fragments, it remains unknown how dispersal between fragments connected by a corridor compares to dispersal in unfragmented landscapes. To assess the extent to which corridors can restore dispersal in fragmented landscapes to levels observed in unfragmented landscapes, we employed a stable‐isotope marking technique to track seeds within four unfragmented landscapes and eight experimental landscapes with fragments connected by corridors. We studied two wind‐ and two bird‐dispersed plant species, because previous community‐based research showed that dispersal mode explains how connectivity effects vary among species. We constructed dispersal kernels for these species in unfragmented landscapes and connected fragments by marking seeds in the center of each landscape with 15 N and then recovering marked seeds in seed traps at distances up to 200 m. For the two wind‐dispersed plants, seed dispersal kernels were similar in unfragmented landscapes and connected fragments. In contrast, dispersal kernels of bird‐dispersed seeds were both affected by fragmentation and differed in the direction of the impact: Morella cerifera experienced more and Rhus copallina experienced less long‐distance dispersal in unfragmented than in connected landscapes. These results show that corridors can facilitate dispersal probabilities comparable to those observed in unfragmented landscapes. Although dispersal mode may provide useful broad predictions, we acknowledge that similar species may respond uniquely due to factors such as seasonality and disperser behavior. Our results further indicate that prior work has likely underestimated dispersal distances of wind‐dispersed plants and that factors altering long‐distance dispersal may have a greater impact on the spread of species than previously thought.

Semiautomated quantitative image analysis of glomerular immunohistochemistry markers desmin, vimentin, podocin, synaptopodin and WT-1 in acute and chronic rat kidney disease models - J. Funk; V. Ott; A. Herrmann; W. Rapp; S. Raab; W. Riboulet; A. Vandjour; E. Hainaut; A. Benardeau; T. Singer; B. Jacobsen (Histochemistry and Cell Biology, 2016)

Differential Accumulation of Mercury and Selenium in Brown Trout Tissues of a High-Gradient Urbanized Stream in Colorado, USA - S. J. Herrmann; D. R. Nimmo; J. S. Carsella; L. M. Herrmann-Hoesing; J. A. Turner; J. M. Gregorich; B. D. Vanden Heuvel; R. B. Nehring; H. P. Foutz (Archives of Environmental Contamination and Toxicology, 2016)

An Overview of the Regional Experiments for Land-atmosphere Exchanges 2012 (REFLEX 2012) Campaign - Wim J. Timmermans; Christiaan van der Tol; Joris Timmermans; Murat Ucer; Xuelong Chen; Luis Alonso; Jose Moreno; Arnaud Carrara; Ramon Lopez; Fernando de la Cruz Tercero; Horacio L. Corcoles; Eduardo de Miguel; et al. (Acta Geophysica, 2015)

Chlamydiaceae-like bacterium, but no Chlamydia psittaci, in sea birds from Antarctica - Jenny Isaksson; Linus Christerson; Maria Blomqvist; Michelle Wille; Lucia A. Alladio; Konrad Sachse; Björn Olsen; Daniel González-Acuña; Björn Herrmann (Polar Biology, 2015)

Photocatalytic abatement results from a model street canyon - M. Gallus; R. Ciuraru; F. Mothes; V. Akylas; F. Barmpas; A. Beeldens; F. Bernard; E. Boonen; A. Boréave; M. Cazaunau; N. Charbonnel; H. Chen; et al. (Environmental Science and Pollution Research, 2015)

Analysing the effect of soil organic matter on bacterial communities using T-RFLP fingerprinting: different methods, different stories? - A. Blaud; F. Diouf; A. M. Herrmann; T. Z. Lerch (Biology and Fertility of Soils, 2015)

Mutations of the SLIT2–ROBO2 pathway genes SLIT2 and SRGAP1 confer risk for congenital anomalies of the kidney and urinary tract - Daw-Yang Hwang; Stefan Kohl; Xueping Fan; Asaf Vivante; Stefanie Chan; Gabriel C. Dworschak; Julian Schulz; Albertien M. van Eerde; Alina C. Hilger; Heon Yung Gee; Tracie Pennimpede; Bernhard G. Herrmann; et al. (Human Genetics, 2015)

Erratum to: Relationships between feeding, growth and swimming activity of European sprat (Sprattus sprattus L.) post-larvae in the laboratory - Myron A. Peck; Jens-Peter Herrmann; Bianca Ewest; Sven Stäcker; Axel Temming (Environmental Biology of Fishes, 2015)

Relationships between feeding, growth and swimming activity of European sprat (Sprattus sprattus L.) post-larvae in the laboratory - Myron A. Peck; Bianca Ewest; Jens-Peter Herrmann; Fahad A. Al-Misned; M. Golam Mortuza; Sven Stäcker; Axel Temming (Environmental Biology of Fishes, 2015)

Chemical properties of HULIS from three different environments - T. B. Kristensen; L. Du; Q. T. Nguyen; J. K. Nøjgaard; C. Bender Koch; O. Faurskov Nielsen; A. G. Hallar; D. H. Lowenthal; B. Nekat; D. van Pinxteren; H. Herrmann; M. Glasius; et al. (Journal of Atmospheric Chemistry, 2015)

Differentiation and Phylogenetic Relationships in Mycobacterium spp with Special Reference to the RNase P RNA Gene rnpB - Björn Herrmann; Pelle Stolt; Guma Abdeldaim; Carl-Johan Rubin; Leif A. Kirsebom; Mikael Thollesson (Current Microbiology, 2014)

Antiphasic 40 Hz Oscillatory Current Stimulation Affects Bistable Motion Perception - Daniel Strüber; Stefan Rach; Sina A. Trautmann-Lengsfeld; Andreas K. Engel; Christoph S. Herrmann (Brain Topography, 2014)

Ground-level hyperspectral imagery for detecting weeds in wheat fields - I. Herrmann; U. Shapira; S. Kinast; A. Karnieli; D. J. Bonfil (Precision Agriculture, 2013)

Modelling multiphase chemistry in deliquescent aerosols and clouds using CAPRAM3.0i - A. Tilgner; P. Bräuer; R. Wolke; H. Herrmann (Journal of Atmospheric Chemistry, 2013)

Reference ranges and cutoff levels of pneumococcal antibody global serum assays (IgG and IgG2) and specific antibodies in healthy children and adults - M. A. Rose; J. Buess; Y. Ventur; S. Zielen; E. Herrmann; J. Schulze; R. Schubert (Medical Microbiology and Immunology, 2013)

Long-term size-segregated particle (PM10, PM2.5, PM1) characterization study at Melpitz -- influence of air mass inflow, weather conditions and season - G. Spindler; A. Grüner; K. Müller; S. Schlimper; H. Herrmann (Journal of Atmospheric Chemistry, 2013)

Biogas Production from Maize: Current State, Challenges and Prospects. 2. Agronomic and Environmental Aspects - A. Herrmann (BioEnergy Research, 2013)

Functional responses of juvenile herring and sprat in relation to different prey types - R. Brachvogel; L. Meskendahl; J.-P. Herrmann; A. Temming (Marine Biology, 2013)

Bioaccumulation of Selenium by the Bryophyte Hygrohypnum ochraceum in the Fountain Creek Watershed, Colorado - S. J. Herrmann; J. A. Turner; J. S. Carsella; D. W. Lehmpuhl; D. R. Nimmo (Environmental Management, 2012)

Particle Size Reduction during Harvesting of Crop Feedstock for Biogas Production I: Effects on Ensiling Process and Methane Yields - C. Herrmann; M. Heiermann; C. Idler; A. Prochnow (BioEnergy Research, 2012)

Particle Size Reduction During Harvesting of Crop Feedstock for Biogas Production II: Effects on Energy Balance, Greenhouse Gas Emissions and Profitability - C. Herrmann; A. Prochnow; M. Heiermann; C. Idler (BioEnergy Research, 2012)

Biogas Production from Maize: Current State, Challenges, and Prospects. 1. Methane Yield Potential - A. Herrmann; J. Rath (BioEnergy Research, 2012)

High gene flow on a continental scale in the polyandrous K entish plover C haradrius alexandrinus - Clemens Küpper; Scott V. Edwards; András Kosztolányi; Monif Alrashidi; Terry Burke; Philipp Herrmann; Araceli Argüelles‐Tico; Juan A. Amat; Mohamed Amezian; Afonso Rocha; Hermann Hötker; Anton Ivanov; et al. (Molecular Ecology, 2012)
Gene flow promotes genetic homogeneity of species in time and space. Gene flow can be modulated by sex‐biased dispersal that links population genetics to mating systems. We investigated the phylogeography of the widely distributed K entish plover C haradrius alexandrinus . This small shorebird has a large breeding range spanning from W estern E urope to J apan and exhibits an unusually flexible mating system with high female breeding dispersal. We analysed genetic structure and gene flow using a 427‐bp fragment of the mitochondrial (mt DNA ) control region, 21 autosomal microsatellite markers and a Z microsatellite marker in 397 unrelated individuals from 21 locations. We found no structure or isolation‐by‐distance over the continental range. However, island populations had low genetic diversity and were moderately differentiated from mainland locations. Genetic differentiation based on autosomal markers was positively correlated with distance between mainland and each island. Comparisons of uniparentally and biparentally inherited markers were consistent with female‐biased gene flow. Maternally inherited mt DNA was less structured, whereas the Z ‐chromosomal marker was more structured than autosomal microsatellites. Adult males were more related than females within genetic clusters. Taken together, our results suggest a prominent role for polyandrous females in maintaining genetic homogeneity across large geographic distances.

H-D exchange on graphite–potassium intercalation compounds - Siegbert Rummel; Michael Herrmann; Manfred Wahren; Safar M. Yunusov; Margarita A. Ilatovskaya; Yuri B. Isaev; N. D. Lapkina; Yuri N. Novikov; Vladimir B. Shur (Isotopes in Environmental and Health Studies, 2012)

Size-segregated characterization of PM10 at the EMEP site Melpitz (Germany) using a five-stage impactor: a six year study - G. Spindler; T. Gnauk; A. Grüner; Y. Iinuma; K. Müller; S. Scheinhardt; H. Herrmann (Journal of Atmospheric Chemistry, 2012)

Modified light use efficiency model for assessment of carbon sequestration in grasslands of Kazakhstan: combining ground biomass data and remote-sensing - Pavel A. Propastin; Martin W. Kappas; Stefanie M. Herrmann; Compton J. Tucker (International Journal of Remote Sensing, 2012)

Resurrecting an extinct species: archival DNA, taxonomy, and conservation of the Vegas Valley leopard frog - Evon R. Hekkala; Raymond A. Saumure; Jef R. Jaeger; Hans-Werner Herrmann; Michael J. Sredl; David F. Bradford; Danielle Drabeck; Michael J. Blum (Conservation Genetics, 2011)

Response of a Coupled Ocean–Atmosphere Model to Greenland Ice Melting - D. Stammer; N. Agarwal; P. Herrmann; A. Köhl; C. R. Mechoso (Surveys in Geophysics, 2011)

Regulation of GDF-15, a distant TGF-β superfamily member, in a mouse model of cerebral ischemia - Katharina Schindowski; Oliver von Bohlen und Halbach; Jens Strelau; Dirk A. Ridder; Oliver Herrmann; Andreas Schober; Markus Schwaninger; Klaus Unsicker (Cell and Tissue Research, 2011)

Seasonal characteristics of tropical marine boundary layer air measured at the Cape Verde Atmospheric Observatory - L. J. Carpenter; Z. L. Fleming; K. A. Read; J. D. Lee; S. J. Moller; J. R. Hopkins; R. M. Purvis; A. C. Lewis; K. Müller; B. Heinold; H. Herrmann; K. Wadinga Fomba; et al. (Journal of Atmospheric Chemistry, 2010)

Obesity is associated with improved survival in patients with organ-confined clear-cell kidney cancer - Sandra Waalkes; Axel S. Merseburger; Mario W. Kramer; Thomas R. W. Herrmann; Gerd Wegener; Julia Rustemeier; Rainer Hofmann; Mark Schrader; Markus A. Kuczyk; Andres J. Schrader (Cancer Causes & Control, 2010)

SWIR-based spectral indices for assessing nitrogen content in potato fields - I. Herrmann; A. Karnieli; D. J. Bonfil; Y. Cohen; V. Alchanatis (International Journal of Remote Sensing, 2010)

Triassic and Jurassic palaeoclimate development in the Junggar Basin, Xinjiang, Northwest China—a review and additional lithological data - A. Rahman Ashraf; Yuewu Sun; Ge Sun; Dieter Uhl; Volker Mosbrugger; Jie Li; Mark Herrmann (Palaeobiodiversity and Palaeoenvironments, 2010)

Effects of temperature and body mass on metabolic rates of sprat, Sprattus sprattus L. - L. Meskendahl; J.-P. Herrmann; A. Temming (Marine Biology, 2010)

Stress by poor food quality and exposure to humic substances: Daphnia magna responds with oxidative stress, lifespan extension, but reduced offspring numbers - Christian E. W. Steinberg; Nadia Ouerghemmi; Steffen Herrmann; Rihab Bouchnak; Maxim A. Timofeyev; Ralph Menzel (Hydrobiologia, 2010)

Disease mutations in the “head” domain of the extra-sarcomeric protein desmin distinctly alter its assembly and network-forming properties - Sarika Sharma; Norbert Mücke; Hugo A. Katus; Harald Herrmann; Harald Bär (Journal of Molecular Medicine, 2009)

Effect of temperature on the gastric evacuation in sprat Sprattus sprattus - M. Bernreuther; A. Temming; J.‐P. Herrmann (Journal of Fish Biology, 2009)
Gastric evacuation of groups of juvenile (mean 63 mm total length, L T , 0·283 g dry mass, M D ) sprat Sprattus sprattus feeding on brine shrimp Artemia sp. nauplii was studied at six temperatures (7·5, 10, 13, 16, 19·5 and 21·5° C) in the laboratory. Gastric evacuation was best described with a general model: , with S t = stomach content at time t , S 0 = stomach content at time 0, t = time , R , B = constants. The shape parameter was estimated as B = 0·668. For comparison with other studies, an exponential model was fitted also to the data. The evacuation constant ( R ) of the general gastric evacuation model increased exponentially with temperature between 7·5 and 16° C. The slope of the increase was reduced between 16 and 19·5° C and a slight decrease was observed between 19 and 21·5° C. Additionally, the effect of mean M D (range 0·286 – 1·025 g) was examined. A simple power function ( ) described the influence of predator mass on exponential evacuation constant with C = 0·503. The results of this investigation were integrated into a consumption model for the calculation of daily rations of S. sprattus : , with T = ambient temperature (°C) and of field stomach contents (g dry) individually raised to the power of 0·668.

Anticipation of natural stimuli modulates EEG dynamics: physiology and simulation - Ingo Fründ; Jeanette Schadow; Niko A. Busch; Nicole Naue; Ursula Körner; Christoph S. Herrmann (Cognitive Neurodynamics, 2008)

Secondary structure and distribution of fusogenic LV-peptides in lipid membranes - J. Ollesch; B. C. Poschner; J. Nikolaus; M. W. Hofmann; A. Herrmann; K. Gerwert; D. Langosch (European Biophysics Journal, 2008)

Incomplete nonsense-mediated decay of mutant lamin A/C mRNA provokes dilated cardiomyopathy and ventricular tachycardia - Stephanie K. Geiger; Harald Bär; Philipp Ehlermann; Sarah Wälde; Désirée Rutschow; Raphael Zeller; Boris T. Ivandic; Hanswalter Zentgraf; Hugo A. Katus; Harald Herrmann; Dieter Weichenhan (Journal of Molecular Medicine, 2008)

Intragenic deletion in the LARGE gene causes Walker-Warburg syndrome - Jeroen van Reeuwijk; Prabhjit K. Grewal; Mustafa A. M. Salih; Daniel Beltrán-Valero de Bernabé; Jenny M. McLaughlan; Caroline B. Michielse; Ralf Herrmann; Jane E. Hewitt; Alice Steinbrecher; Mohamed Z. Seidahmed; Mohamed M. Shaheed; Abdullah Abomelha; et al. (Human Genetics, 2007)

Genetic diversity and mass resources promote colony size and forager densities of a social bee ( Bombus pascuorum ) in agricultural landscapes - FARINA HERRMANN; CATRIN WESTPHAL; ROBIN F. A. MORITZ; INGOLF STEFFAN‐DEWENTER (Molecular Ecology, 2007)
Although habitat fragmentation and agricultural intensification are known as threads to pollinator diversity, little is known about consequences for population size and genetic diversity. Here, we combined detailed field observations, molecular approaches and GIS‐based quantification of landscape structure (measured by proportions of seminatural habitats and proportions of mass flowering crops) to get new insights into driving forces of population dynamics of the bumblebee species Bombus pascuorum . Comparing 13 agriculturally dominated landscape sectors, we found the proportion of mass flowering crops to positively influence bumblebee abundance whereas the proportion of seminatural habitats was of minor importance. We used microsatellites to quantify landscape‐related colony densities, inbreeding and population substructure. Detected colony densities did not correlate with landscape parameters or with local worker abundance, measured by field observations. These results indicate that increased worker abundances within landscapes are rather due to greater colony sizes than due to an increased number of nests. We found significant population substructure, measured by F ST and seven landscape sectors to bear significantly increased inbreeding values ( F IS ). F IS was strongly varying between sectors but did not correlate with landscape structure. Moreover, F IS had a significantly negative effect on colony size, demonstrating the importance of genetic diversity on population fitness at a landscape scale. We suggest that inbreeding levels might be related to the temporal variation of food resources and population sizes in agricultural landscapes.

A source study of PM in Saxony by Size-Segregated Characterisation - H. Herrmann; E. Brüggemann; U. Franck; T. Gnauk; G. Löschau; K. Müller; A. Plewka; G. Spindler (Journal of Atmospheric Chemistry, 2006)

Root-to-shoot signalling: apoplastic alkalinization, a general stress response and defence factor in barley (Hordeum vulgare) - H. H. Felle; A. Herrmann; R. Hückelhoven; K.-H. Kogel (Protoplasma, 2005)

From Single Genes to Co-Expression Networks: Extracting Knowledge from Barley Functional Genomics - P. Faccioli; P. Provero; C. Herrmann; A. M. Stanca; C. Morcia; V. Terzi (Plant Molecular Biology, 2005)

Frequency of Norovirus in stool samples from patients with gastrointestinal symptoms in Switzerland - R. Fretz; L. Herrmann; A. Christen; P. Svoboda; O. Dubuis; E. H. Viollier; M. Tanner; A. Baumgartner (European Journal of Clinical Microbiology & Infectious Diseases, 2005)

Ontogenic changes in the allometric scaling of the mass and length relationship in Sprattus sprattus - M. A. Peck; C. Clemmesen; J.‐P. Herrmann (Journal of Fish Biology, 2005)
An analysis of mass ( M ) and standard length ( L S ) data for larval, juvenile and adult sprat ( Sprattus sprattus ; Clupeidae) revealed marked changes in the allometric scaling factor ( b in ). For sprat L S , b was 5·0, whereas in larger juveniles and adults, b was c. 3·4 indicating a relatively protracted metamorphic period for this species.

Comparative analysis of adenoviral transgene delivery via tail or portal vein into rat liver - J. Herrmann; B. Abriss; E. van de Leur; S. Weiskirchen; A. M. Gressner; R. Weiskirchen (Archives of Virology, 2004)

Size-Resolved Aerosol Characterization for a Polluted Episode at the IfT Research Station Melpitz in Autumn 1997 - A. Plewka; T. Gnauk; E. Brüggemann; C. Neusüss; H. Herrmann (Journal of Atmospheric Chemistry, 2004)

Iron overload in adult Hfe-deficient mice independent of changes in the steady-state expression of the duodenal iron transporters DMT1 and Ireg1/ferroportin - Thomas Herrmann; Martina Muckenthaler; Frank van der Hoeven; Karen Brennan; Sven G. Gehrke; Nadia Hubert; Consolato Sergi; Hermann-Josef Gröne; Iris Kaiser; Isabella Gosch; Martin Volkmann; Hans-Dieter Riedel; et al. (Journal of Molecular Medicine, 2004)

Treatment of Severe Candida Infections in High-Risk Patients in Germany: Consensus Formed by a Panel of Interdisciplinary Investigators - Büchner T.; Fegeler W.; Bernhardt H.; Brockmeyer N.; Duswald K.-H.; Herrmann M.; Heuser D.; Jehn U.; Just-Nübling G.; Karthaus M.; Maschmeyer G.; Müller F.-M.; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2002)

C-to-U conversion in the intercistronic ndhI/ndhG RNA of plastids from monocot plants: conventional editing in an unconventional small reading frame? - A. Drescher; H. Hupfer; C. Nickel; F. Albertazzi; U. Hohmann; R. Herrmann; R. Maier (Molecular Genetics and Genomics, 2002)

Noise and the PSTH Response to Current Transients: II. Integrate-and-Fire Model with Slow Recovery and Application to Motoneuron Data - A. Herrmann; W. Gerstner (Journal of Computational Neuroscience, 2002)

Noise and the PSTH Response to Current Transients: I. General Theory and Application to the Integrate-and-Fire Neuron - A. Herrmann; W. Gerstner (Journal of Computational Neuroscience, 2001)

N budget and NH3 exchange of a grass/clover crop at two levels of N application - B. Herrmann; S. K. Jones; J. Fuhrer; U. Feller; A. Neftel (Plant and Soil, 2001)

Gastric evacuation in horse mackerel. I. The effects of meal size, temperature and predator weight - A. Temming; J.‐P. Herrmann (Journal of Fish Biology, 2001)
Gastric evacuation experiments were performed on horse mackerel Trachurus trachurus. A nearly full matrix experimental design with respect to the variables predator weight ( Osmerus eperlanus as prey. A general evacuation model without meal size as a variable was fitted to the data on wet weights as well as on dry weights by means of non‐linear regression technique. Two methods of data transformation, relative data and square root transformation, were applied to improve variance homogeneity. The most reliable model fit was achieved on dry weight data applying the square root transformation technique: image where S t =stomach content (g wet weight) at time t after ingestion, S 0 =the initial meal size, W =predator (g wet weight), and T =temperature. The estimated coefficient of the exponential temperature function, δ=00·032, corresponds to a Q 10 value of 1·4 which is outstandingly low in comparison with results on other species. However additional experiments to determine maximum daily food rations indicated that appetite in contrast to gastric evacuation is strongly temperature dependent.

Gastric evacuation of horse mackerel. II. The effects of different prey types on the evacuation model - A. Temming; J.‐P Herrmann (Journal of Fish Biology, 2001)
Gastric evacuation experiments were performed on horse mackerel Trachurus trachurus. Discrete meals of different sizes of krill Meganyctiphanes norvegicus, mysids Neomysis integer , brown shrimp Crangon crangon , and herring Clupea harengus were fed to test the effect of prey type on the gastric evacuation. A general evacuation model without meal size as a variable was fitted to the data on dry weights by means of non‐linear regression. With the exception of mysid evacuation the estimated parameters for curvature, predator weight effect, and temperature effect of the general evacuation model were very similar for all other food types and also confirmed the results obtained with smelt Osmerus eperlanus. In contrast the evacuation of mysids showed a strong exponential curvature, rather the effect of prey size than of prey type. The prey specific evacuation constants of the model revealed a linear relationship to the energy content. A general consumption model for field estimates is presented that can be used for prey types that have not yet been tested in the experiments, provided the energy content is known.

Biosphere-atmosphere interactions of ammonia with grasslands: Experimental strategy and results from a new European initiative - M.A. Sutton; C. Milford; E. Nemitz; M.R. Theobald; P.W. Hill; D. Fowler; J.K. Schjoerring; M.E. Mattsson; K.H. Nielsen; S. Husted; J.W. Erisman; R. Otjes; et al. (Plant and Soil, 2001)

Analysis of single-nucleotide polymorphisms in the interleukin-4 receptor gene for association with inflammatory bowel disease - M. Olavesen; J. Hampe; M. M. Mirza; R. Saiz; C. M. Lewis; S. Bridger; D. Teare; D. F. Easton; T. Herrmann; G. Scott; J. Hirst; J. Sanderson; et al. (Immunogenetics, 2000)

Lipid domains in the exoplasmic and cytoplasmic leaflet of the human erythrocyte membrane: a spin label approach - Marta Zuvic-Butorac; Peter Müller; Thomas Pomorski; Jeanette Libera; A. Herrmann; Milan Schara (European Biophysics Journal, 1999)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

Effect of dimethicone (polysilane gel) on the stereoselective pharmacokinetics of ketoprofen - N. Presle; F. Lapicque; P. Gillet; M.-A. Herrmann; B. Bannwarth; P. Netter (European Journal of Clinical Pharmacology, 1998)

Tissue culture of wild-type, interspecific genome/plastome hybrids and plastome mutants of evening primrose ( Oenothera) : controlled morphogenesis and transformation - A. Mehra-Palta; H.-U. Koop; S. Goes; E.-M. Troidl; G. Nagy; S. Tyagi; W. Kofer; R. G. Herrmann (Plant Cell Reports, 1998)

Biophysical characterization of the interaction of bovine seminal plasma protein PDC-109 with phospholipid vesicles - Peter Müller; Karl-Rudolf Erlemann; Karin Müller; Juan J. Calvete; Edda Töpfer-Petersen; Kathleen Marienfeld; A. Herrmann (European Biophysics Journal, 1998)